Ethnic Stereotyping and Intra-Religious Conflict: The Experience of Muslims in Sambas of the Indonesian West Borneo - Syamsul Kurniawan; Sangkot Sirait; Azis Muslim (Graduate Program of Pontianak Institute of Islamic Studies, 2021)
This paper aims to explore the impact of ethnic differences and ethnic stereotyping on the atmosphere of peace, written based on the conflict event between Muslims of different ethnicities (ethnic Malay of Sambas and ethnic Madurese) in Sambas in 1999. This paper, based on my research from 2018, is qualitative research with data obtained from observation, interviews, and documentation. Regarding the method, this research used a qualitative method that leads to a case study model as an investigative method. Meanwhile, for data analysis, the interactive data analysis method using the theory of self-categorization was employed. Based on the findings of the study, ethnic differences and stereotypes had a significant impact on the escalation of conflict between Muslims in Sambas in 1999. These ethnic differences and stereotypes essentially emerged as a consequence of the way a person or group of people of a particular ethnicity categorizes a person or group of people of another ethnicity.